Upaya Meningkatkan Sikap Tanggung Jawab Dengan Menggunakan Magic Box Berbasis Wayang Sukuraga Di Sekolah Dasar - Dede Aliah; Iis Nurasiah; Dyah Lyesmaya (FKIP, Universitas Palangka Raya, 2024)
This study aims to determine the increase in students' responsible attitude by using the Magic Box learning media based on Wayang Sukuraga at SDN 1 Kebon Pedes. The research method used is Classroom Action Research which consists of two cycles. Each cycle begins with the stages of planning, implementing, observing and reflecting. The instruments used were teacher and student observation sheets as well as non-test assessments. The results of the study show that the application of the Magic Box learning media based on wayang sukuraga can increase the attitude of responsibility of students at SDN 1 Kebon Pedes. This can be seen from the results of data processing obtained in cycle 1, as many as 10 students out of 26 total students have an increased attitude of responsibility while the other 16 students do not yet have an attitude of responsibility, so that the percentage of attitudes of responsibility reaches 40% with an average value 67.76. In cycle 2 the results of processing the data obtained were 22 students out of 26 the total number of students had an increased attitude of responsibility with a percentage of 85% and the average value was 76.34